The Role of Dispositional Optimism, Upward and Downward Counterfactual Thinking towards Student Persistence in Joining Competitions - Maria Gracia Amara Pawitra; Wahyu Jati Anggoro (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Persistence is a key element contributing to college students’ success in an academic competition. We argue that dispositional optimism, and upward and downward counterfactual thinking have influence in determining individuals’ persistence. This cross-sectional study aimed to examine the role of dispositional optimism, upward and downward counterfactual thinking among persistence of student participants in university competitions. It employed quantitative methods and data were collected through the use of Dispositional Optimism Scale, Counterfactual Thinking Scale, and Persistence Scale. College students (N=204) who have competed in university competitions were recruited using a non-probability sampling method. Multiple regression assisted the data analysis process. Result showed that both dispositional optimism and upward counterfactual thinking simultaneously predicted students’ persistence. However, downward counterfactual thinking was unable to predict the students’ persistence. The research suggests that student competitors should enhance their optimism by developing positive thoughts concerning future competitions, as well as forming upward counterfactual thinking in subsequent competitions.